A Prototype of a Wirelessly Controlled Nuclear Centrifuge (International Journal of Engineering and Computer Science, 2014)
Centrifuge is a device used to separate materials from each other based on certain percentages. A nuclear centrifuge is a device that performs isotope separation of gases. It is used to separate uranium-235 from uranium-238. To perform the separation process, uranium hexafluoride gas is placed in a hollow cylinder and rotated at a high speed. This rotation creates a strong centrifugal force so that the heavier gas, U-238 is thrown towards the edge. The lighter U-235 moves up where it is collected. In this paper a prototype that simulates a nuclear centrifuge was designed using DC motors that operate at different speeds to perform the separation process. The centrifuge was wirelessly controlled allowing people working in that area to control it from a distance without being exposed to radiation and toxic chemicals.